Pendugaan Peptida Bioaktif Cadangan Protein Koro Pedang Hasil Hidrolisis Protease Tubuh Melalui Pendekatan In Silico - Maida, Marciano Oscar; Sitanggang, Azis Boing; Budijanto, Slamet (Jurnal Teknologi dan Industri Pangan, 2025)
The jack bean plant (Canavalia ensiformis L.) contains storage proteins composed of essential amino acids, and the biological activity of these components occurs after a hydrolysis process. The hydrolysis of peptide bonds that appear in the digestive tract can be identified using an in silico approach that utilises a bioinformatics web page. This study aims to predict bioactive peptides resulting from the hydrolysis of storage proteins in the jack beans using a web-based in silico method. Based on literature studies, the jack bean’s dominant storage proteins include canavalin, concanavalin A, and concanavalin B. The amino acid sequences of each type of protein were obtained from the Universal Protein Resource (UniProt) page. Simulations of hydrolysis or cleavage of peptide bonds in the body using Gastrointestinal System (GIS) enzymes, in the form of pepsin, trypsin, and chymotrypsin or a combination thereof, were carried out in the Expert Protein Analysis System (ExPASy) portal on the Peptide Cutter page. The bioactive peptides resulting from the cleavage were identified for their suitability based on the literature using the BIOPEP-UWM database. The simulation results indicate that all jack bean storage proteins possess biological properties, including antihypertensives, antidiabetics, and antioxidant effects. Concanavalin A produced the highest bioactive peptide yield of 82.89%, followed by concanavalin B at 64.23%, and canavalin at 48.95%. The estimation of bioactive peptides from jack bean storage proteins by hydrolysis of body proteases using an in silico approach proved helpful. It can be further applied to other protein sources using different enzyme combinations.